ASM-based formal design of an adaptivity component for a Cloud system. (July 2016) - Arcaini, Paolo; Holom, Roxana-Maria; Riccobene, Elvinia
Abstract The request of formal methods for the specification and analysis of distributed systems is nowadays increasing, especially when considering the development of Cloud systems and Web applications. This is due to the fact that modeling languages currently used in these areas have informal definitions and ambiguous semantics, and therefore their use may be unreliable. Thanks to their mathematical foundation, formal methods can guarantee rigorous system design, leading to precise models where requirements can be validated and properties can be assured, already at the early stages of the system development. In this paper, we present a rigorous engineering process for distributed systems, based on the Abstract State Machines (ASM) formal method. We rely on the foundational notions of ASM ground model and model refinement to obtain a precise model for a client-server application for Cloud systems. This application has been proposed to tackle the problem of making Cloud services usable to different end-devices by adapting on-the-fly the content coming from the Cloud to the different devices contexts. The ASM-based modeling process is supported by a number of validation and verification activities that have been exploited on the component under development to guarantee consistency, correctness, and reliability properties.